2021 Guideline for the Prevention of Stroke in Patients With Stroke and Transient Ischemic Attack: A Guideline From the American Heart Association/American Stroke Association. Issue 7 (July 2021) - Kleindorfer, Dawn O.; Towfighi, Amytis; Chaturvedi, Seemant; Cockroft, Kevin M.; Gutierrez, Jose; Lombardi-Hill, Debbie; Kamel, Hooman; Kernan, Walter N.; Kittner, Steven J.; Leira, Enrique C.; Lennon, Olive; Meschia, James F.; et al.
Abstract : Supplemental Digital Content is available in the text.